Strategic Efforts of Islamic Boarding Schools in Developing the Value Chain of the Halal Ecosystem in Dumai City - Daharmi Astuti; Boy Syamsul Bakhri; Jimmi Pasla (Proceeding International Conference on Social Sciences, 2026)
This research is motivated by the rapid growth of the global halal industry, which continues to expand, including in Indonesia. The Governor of Riau has designated Riau as one of the national halal destinations due to its strategic location near Malay countries. The development of the halal industry in Riau is supported by government policies that implement Islamic standards from upstream to downstream sectors. Islamic boarding schools (pesantren) as socio-economic entities play an important role in the value chain of the halal ecosystem. Dumai City, known as the “City of Dreams,” has been declared a halal industrial zone. However, the city faces five major challenges: drug abuse, promiscuity, HIV/AIDS, LGBT issues, and the spread of heretical teachings. These challenges contradict the vision of establishing a halal city. This study aims to analyze the efforts and roles of pesantren business units as drivers of the halal ecosystem capable of creating social change and influencing community behavior. Using a descriptive qualitative method involving three pesantren in Dumai City, the findings indicate that pesantren can serve as exemplary institutions in applying Islamic values to economic practices through the principles of honesty, justice, balance, trustworthiness, and the avoidance of riba(usury). Interviews also revealed that pesantren administrators instill four main principles in managing economic activities—honesty, trustworthiness (amanah), public benefit (maslahah), and freedom from riba. In conclusion, pesantren can serve as role models for the community in integrating Islamic values into economic activities and implementing sharia principles in everyday life.